PENGARUH KONSENTRASI ETANOL TERHADAP PENJERAPAN NIFEDIPIN PADA FORMULA ETHOSOME - Rizal, Rizal; Ismail, Isriany (Jurnal Farmasi Indonesia, 2018)
Researched about the influence of ethanol consentration to entrapment of nifedipin in ethosome formula. This research suppose to know about the influence of etanol consentration tonifedipine entrapment, form and size of ethosome, to decide the optimal consentration of etanol forming ethosome with high PDE (Percent Drug Entrapment) in nifedipin, and to know the ethosome characteristic. Ethosome formula made in by hot method, using variation consentration of ethanol, phosphatidilcholin 1.5% and nefidepin 0,05%. Nifedipin concentration that entrapment in ethosome measured byUV-VIS Spectrophotometer at wavelength 336 nm, form and ethosome size fixed by using microscope. Ethosome with high percent drug entrapment have taken from formula by using ethanol 50% with entrapment 71.440%. The formed ethosome is Multy Lameral Vesicle (MLV) and Multy Vesicular Vesicle (MVV) with the size about 1 μm until 15μm.